Dosis de compost de residuos sólidos orgánicos domiciliarios en el rendimiento Coriandrum sativum L., culantro. Loreto, Perú. 2024 - Rodriguez Chuquipiondo, Jezmin Edelmira (2024)
The study on the dose of compost from household organic waste in the cultivation of coriander (Coriandrum sativum L.) was developed in the region of Loreto, in a clay loam soil located in the Horticultural Plant Workshop of the Faculty of Agronomy of the UNAP, whose main objective was to evaluate its effects on the agronomic components and yield of the crop. The statistical design was the DBCA, with four replications, the ANVA and the Tukey test to obtain the significances between Blocks and Treatments. The results indicated that there are no statistical differences in the agronomic components; but, if in the yield, highlighting the T4 treatment with the application of 50 t of compost/ha obtaining 10,512 Kg/ha and the T3 with 40 t of compost/ha, with 10,080 Kg/ha, being considered as the one with the best economic benefit the T3, with S/.25,303.4.